Transcriptomics-based investigation of resistance differences to swine fever between large white pigs and min pigs - Jia Li; Deming Ren; Xiangxu Meng; Yiyun He; Lixian Wang; Xihui Sheng; Ligang Wang (Virus Research)
The genetic foundations underlying the observed disease resistance in certain indigenous pig breeds, notably the Min pigs of China, present a compelling underexplored subject of study. Exploring the mechanisms of disease resistance in these breeds could lay the groundwork for genetic improvements in pig immunity, potentially augmenting overall pig productivity. In this study, whole blood samples were collected from pre- and post- swine fever vaccinated Min and Large White pigs for transcriptome sequencing. The mRNA and lncRNA in both pig breeds were analyzed, and intra-group and inter-group comparisons were also conducted. The results indicated that a greater number of immune-related pathways such as the JAK-STAT and PI3K-AKT signaling were enriched in Min pigs. Furthermore, genes involved in inflammation and antiviral responses, including IL16, IL27, USP18, and DHX58, were upregulated in post-vaccination Min pigs compared to post-vaccination Large White pigs. This heightened immune responsiveness could contribute to the observed differences in disease resistance between Min pigs and Large White pigs.